Mindfulness: Its Transformative Potential for Consumer, Societal, and Environmental Well-Being. (September 2016) - Bahl, Shalini; Milne, George R.; Ross, Spencer M.; Mick, David Glen; Grier, Sonya A.; Chugani, Sunaina K.; Chan, Steven S.; Gould, Stephen; Cho, Yoon-Na; Dorsey, Joshua D.; Schindler, Robert M.; Murdock, Mitchel R.; et al.
The authors propose that mindfulness is an antidote to mindless consumption, which adversely affects individual and collective well-being. The concept of mindfulness is explained and applied to the consumption context. More specifically, the authors examine mindful consumption as an ongoing practice of bringing attention, with acceptance, to inner and outer stimuli, and the effects of this practice on the consumption process. The transformative potential of mindful consumption is reviewed across domains of consumer, societal, and environmental well-being, with suggestions for future research. The article highlights some of the challenges to realizing the transformative potential of mindful consumption and concludes with suggestions for the actions that consumers, institutions, and policy makers could take to promote mindful consumption.